Exogenous 10 kDa-Heat Shock Protein Preserves Mitochondrial Function After Hypoxia/Reoxygenation - Leonardo Maciel; Dahienne Ferreira de Oliveira; Gustavo Monnerat; Gustavo Monnerat; Antonio Carlos Campos de Carvalho; Antonio Carlos Campos de Carvalho; Jose Hamilton Matheus Nascimento (Frontiers Media S.A., 2020)
Humoral factors released during ischemic preconditioning (IPC) protect the myocardium against ischemia/reperfusion (I/R) injury. We have recently identified 10 kDa-heat shock protein (HSP10) and a fraction of small 5-10 kDa peptides (5-10-sP) in the coronary effluent of IPC-treated hearts and demonstrated their cardioprotective potential. We here used our isolated mitochondria model to characterize the impact of exogenous HSP10 and 5-10-sP on mitochondria function from myocardium subjected to I/R injury. Isolated perfused rat hearts were submitted to 30-min global ischemia and 10-min reperfusion. Before ischemia, isolated hearts were infused with saline or 5-10-sP, with or without a mitochondrial ATP-sensitive-K+-channel blocker (5HD 10 μmol·L−1) or PKC inhibitor (chelerythrine 10 μmol·L−1), before I/R. HSP10 (1 µmol·L−1) was infused into isolated hearts before I/R without blockers. At 10-min reperfusion, the mitochondria were isolated and mitochondrial function was assessed. In a subset of experiments, freshly isolated mitochondria were directly incubated with HSP10 or 5-10-sP with or without 5HD or chelerythrine before in vitro hypoxia/reoxygenation. Infusion of 5-10-sP (n = 5) and HSP10 (n = 5) into isolated hearts before I/R improved mitochondrial ADP-stimulated respiration, ATP production and prevented mitochondrial ROS formation compared to the I/R group (n = 5); this effect was abrogated by 5HD and chelerythrine. In freshly isolated mitochondria with in vitro hypoxia/reoxygenation, HSP10 (n = 16) and 5-10-sP (n = 16) incubation prevented reductions of mitochondrial ADP-stimulated respiration (91.5 ± 5.1 nmol O2/min/mg PTN), ATP production (250.1 ± 9.3 μmol ATP/200μg PTN), and prevented mitochondrial ROS production (219.7 ± 9.0 nmol H2O2/200μg PTN) induced by hypoxia/reoxygenation (n = 12, 51.5 ± 5.0 nmol O2/min/mg PTN; 187 ± 21.7 μmol ATP/200 μg PTN; 339.0 ± 14.3 nmol H2O2/200 μg PTN, p < 0.001, respectively). 5HD reduced the ADP-stimulated respiration in the HSP10 group (65.84 ± 3.3 nmol O2/min/mg PTN), ATP production (193.7 ± 12.1 μmol ATP/200μg PTN) and increased ROS in the 5-10-sP group (274.4 ± 21.7 nmol H2O2/200 μg PTN). Mitochondria are a target of the cardioprotection induced by 5-10-sP and HSP10. This protection is dependent of PKC and mKATP activation. HSP10 can act directly on mitochondria and protects against hypoxia/reoxygenation injury by mKATP activation.